2017
DOI: 10.1111/sms.12974
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac imaging to detect coronary artery disease in athletes aged 35 years and older. A scoping review

Abstract: Sudden cardiac death (SCD) is a devastating event in athletes. Screening efforts that were first directed at athletes younger than 35 years are now focusing on the rapidly growing group of older sportspersons. Athletes aged ≥35 years have a 10-fold increased risk of exercise-related cardiac arrest, mostly due to coronary artery disease (CAD). Although cardiac imaging is pivotal in identifying CAD, the role of imaging modalities in screening asymptomatic older sportspersons remains unclear. We performed a scopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 51 publications
0
14
0
2
Order By: Relevance
“…However, high-intensity endurance training could also have adverse potential effects on the heart, such as electrophysiological abnormalities (5) and elevated cardiac markers, including creatine kinase-MB, troponin T and NT-pro brain natriuretic peptide (2). Braber et al (6) indicated that high-intensity endurance training maybe associated with accelerated progression of coronary atherosclerosis and that coronary heart disease remained the leading cause of death for high-intensity endurance athletes over the age of 35. MF is a condition involving the significant increase of collagen volume in myocardial tissue, which results from myocardial tissue injury caused by myocardial ischemia (hypoxia), inflammation and hypertension overload (7). Specific types of MF are associated with ventricular arrhythmia and adverse cardiac events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, high-intensity endurance training could also have adverse potential effects on the heart, such as electrophysiological abnormalities (5) and elevated cardiac markers, including creatine kinase-MB, troponin T and NT-pro brain natriuretic peptide (2). Braber et al (6) indicated that high-intensity endurance training maybe associated with accelerated progression of coronary atherosclerosis and that coronary heart disease remained the leading cause of death for high-intensity endurance athletes over the age of 35. MF is a condition involving the significant increase of collagen volume in myocardial tissue, which results from myocardial tissue injury caused by myocardial ischemia (hypoxia), inflammation and hypertension overload (7). Specific types of MF are associated with ventricular arrhythmia and adverse cardiac events.…”
Section: Introductionmentioning
confidence: 99%
“…However, high-intensity endurance training could also have adverse potential effects on the heart, such as electrophysiological abnormalities ( 5 ) and elevated cardiac markers, including creatine kinase-MB, troponin T and NT-pro brain natriuretic peptide ( 2 ). Braber et al ( 6 ) indicated that high-intensity endurance training maybe associated with accelerated progression of coronary atherosclerosis and that coronary heart disease remained the leading cause of death for high-intensity endurance athletes over the age of 35.…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve a heart rate < 65, short acting beta-blocking agents are used when appropriate. A meta-analysis found that cardiac death or MI occurred in 0.04 % of subjects with no CAD on CCTA, as compared with 1.29 % in subjects with non-obstructive CAD and 6.53 % of subjects with obstructive lesions(166).Echocardiography alone has limited value in identification of CAD, but is an important imaging modality for assessing structural cardiac abnormalities(163).CMR allows for excellent assessment of cardiac function and of LGE without exposure to radiation(163). CMR angiography for anatomical assessment of the coronary arteries is a novel tool with the advantage of no radiation exposure.…”
mentioning
confidence: 99%
“…CMR angiography for anatomical assessment of the coronary arteries is a novel tool with the advantage of no radiation exposure. This method however, still offers limited visualization of the coronary arteries, and is currently most used in research(163,165).Invasive coronary angiography is not a first-line test in low-risk subjects due to the higher risk of complications as compared with non-invasive imaging modalities. It uses intravenous contrast and exposes the patient to radiation (2-7 mS) (6).…”
mentioning
confidence: 99%
“…Recently, several groups have reported a prevalence of coronary artery disease (CAD) of 40-63% in master athletes. [10][11][12] We have reported elevated post-exercise cTn values following strenuous exercise in asymptomatic subjects with occult CAD. 6 Subjects included in the present study were 50-74 years of age.…”
mentioning
confidence: 96%